Spiral of Silence: Consumer Attention, Media Emotion, and Pork Price Fluctuations - Xia Li (Agriculture)
This study utilized web crawling and text analysis to collect weekly data from July 2018 to March 2022. Using the spiral of silence theoretical framework, it explores the relationship between consumer online attention during sudden animal epidemics and pork price volatility. The research found that consumer online attention, influenced by animal disease outbreaks, significantly intensifies pork price volatility both directly and indirectly through changes in media sentiment and consumer expectations. On the one hand, the sentiment in official media reports partially mediates the relationship between consumer attention and pork price volatility. As consumer attention increases, positive sentiment in official media also rises, exerting an indirect stabilizing effect on pork prices. On the other hand, consumer expectations also have a partial mediating role, and the volume of negative news reports from unofficial media significantly amplifies the impact of consumer attention on pork price volatility. These findings provide valuable insights into the relationship between consumer online attention and market fluctuations in the agricultural sector and offer practical recommendations for enhancing demand-side management strategies.